Evaluation of program of community learning activities center (PKBM) in Batam City Province of Riau Islands - Chaidir, Mohammad; Suryadi; Komala, Madha (Technium Social Sciences Journal, 2020)
The purpose of this study was to conduct an evaluation of the community learning activity center program, the background of the holding of this training program was to achieve equitable education, the legal foundation provided in this study was based on the regulation from the Riau Islands province, and the strategy of implementing the community learning center program ( PKBM) was carried out in Batam, the research method used in this study was qualitative, there were five schools used as research subjects. The evaluation carried out at the design stage is related to the policy of implementing community learning program programs in Riau Islands Province. The draft policy must be in place and finalized before the policy is implemented. Policy design is very necessary before a policy is implemented because it will provide clearer direction in setting the steps that must be taken when implementing the policy. Aspects related to the policy design of the implementation of community learning programs include the legal basis, objectives and strategies. Based on the evaluation of the design of the central policy of community learning activities can be said to have been good because there are clear objectives, legal foundation and institutional functions, the implementation of the package equality education program is based on the needs of the community, the existence of a clear package package equality program and the existence of clear and good program achievement indicators